2008
DOI: 10.4049/jimmunol.180.2.688
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Anti-Tumor Necrosis Factor Therapy in Rheumatoid Arthritis Inhibits Memory B Lymphocytes via Effects on Lymphoid Germinal Centers and Follicular Dendritic Cell Networks

Abstract: Rheumatoid arthritis (RA) is mediated by a proinflammatory cytokine network with TNF at its apex. Accordingly, drugs that block TNF have demonstrated significant efficacy in the treatment of RA. A great deal of experimental evidence also strongly implicates B cells in the pathogenesis of RA. Yet, it remains unclear whether these two important players and the therapies that target them are mechanistically linked. In this study we demonstrate that RA patients on anti-TNF (etanercept) display a paucity of follicu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
111
3
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(136 citation statements)
references
References 28 publications
14
111
3
4
Order By: Relevance
“…Both cytokines independently or complementarily enhanced the immune responses and augmented inflammation by targeting various immune cells. Particularly, TNF-a has been established as a central player in the pathogenesis of RA (41), TNF-b is required for the formation of germinal center-like structures within the inflamed synovium (42), and our unpublished data suggest that the CD137 expression on peripheral B cells is elevated in autoimmunity (e.g., RA). Therefore, our data suggest that CD137-mediated B cell stimulation might be involved in the pathogenesis of RA.…”
Section: Discussionmentioning
confidence: 99%
“…Both cytokines independently or complementarily enhanced the immune responses and augmented inflammation by targeting various immune cells. Particularly, TNF-a has been established as a central player in the pathogenesis of RA (41), TNF-b is required for the formation of germinal center-like structures within the inflamed synovium (42), and our unpublished data suggest that the CD137 expression on peripheral B cells is elevated in autoimmunity (e.g., RA). Therefore, our data suggest that CD137-mediated B cell stimulation might be involved in the pathogenesis of RA.…”
Section: Discussionmentioning
confidence: 99%
“…One recent study has shown that TNFa blockade reduces the ability of lymphoid tissue to form germinal centers and decreases the number of follicular dendritic cells, raising the possibility that a perturbed germinal center environment induced by TNFa blockade may promote the emergence of a neoplastic B-cell clone. 26 Specific mechanisms by which blockade of CD25, CD11a, or IL-1 receptor signaling may promote lymphoma are unknown. In our series, anti-CD11a therapy was associated with lymphomas (two cases) and non-lymphomatous lymphoid proliferations (one case), with all cases positive for EBV.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, our findings suggest that APCs for B cells of hematopoietic origin, which are significantly depleted after stem cell transplantation, would be largely dispensable for proper reactivation of virusspecific MBCs. Finally, our studies presented herein warrant investigations of the reactivation of virus-specific MBCs under conditions of long-term TNF/LT blockade, which is frequently used for the treatment of rheumatoid arthritis and psoriasis, as it has been recently suggested from the analysis of FDCs and MBC populations in these patients (48).…”
mentioning
confidence: 99%